Political Economy of Import Waste Regulations in East Java: Implications of Indonesia's Role as Waste Importer Country - Maria Indira Aryani; Aldira Mara Ditta Caesar Purwanto (Future Science, 2020)
Waste management is a significant problem faced by the world on a global scale. Globally, the People's Republic of China (PRC) is the country with the most extensive waste trade in the world as the leading export destination country for recycled waste materials. However, the PRC changed its solid waste import policy by issuing a National Sword policy, which aims to limit and tighten plastic waste imports. The PRC policy change's impact is the increased flow of waste imports to Indonesia, thus placing Indonesia in a